(untitled) (Journal of Science and Technology Research, 2024)
Cereals and pseudograins are known for their bioactive components and hence used as functional food worldwide. Recently, locally grown cheena, kaon, quinoa, and chia are available in Bangladeshi markets. The study aimed to determine the macronutrients, polyphenols, and flavonoids contents of selected cereals (bajra, zob, cheena, and kaon) and pseudograins (quinoa and chia) along with their antioxidant properties. Cheena (13.48%) and kaon (13.55%) showed higher protein content among cereals, whereas chia of commercial and local sources showed high quantities of protein (22.40% and 22.35%, respectively) among pseudograins. A high amount of carbohydrate was found in kaon and quinoa (64.57% and 59.79%, respectively), whereas chia contained a high amount of fat (20.88 to 29.77%) and dietary fiber (31.46% to 36.85%). Locally grown bajra exhibited a markedly higher concentration of total phenolics (135.75±0.33 mg/g GAE dw) and total flavonoids (17.44±0.05 mg/gm QE dw) compared to other foods studied. Regarding antioxidant activity determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and half-maximal inhibitory (IC50) values, chia from Dinajpur field showed the best results. Therefore, cereals and pseudograins studied and reported here could provide utilizable nutritional and functional bioactive polyphenolic components that may have the potential in the nutritional management of noncommunicable diseases. J. of Sci. and Tech. Res. 6(1): 89-98, 2024